Running through the Who, Where, and When: A Cross-cultural Analysis of Situational Changes in Comics. Issue 9 (21st October 2022) - Klomberg, Bien; Hacımusaoğlu, Irmak; Cohn, Neil
ABSTRACT: Understanding visual narratives requires readers to track dimensions of time, spatial location, and characters across a sequence. Previous work has found situational changes across adjacent panels differ cross-culturally, but few works have examined such situational dimensions across extended sequences. We therefore investigated situational "runs" – uninterrupted sequences of the situational dimensions (time, space, characters) – in a corpus of 300+ annotated comics from the United States, Europe, and Asia. We compared runs' proportion and average lengths and found that across books, semantic information changed frequently and run length correlated with proportion. Yet, cross-cultural patterns arose, with American and European comics using more continuous runs than Asian comics. American and European comics also used more and longer temporal and character continuity, while Asian comics used more spatial continuity. These findings raise questions about comprehenders' processing strategies of visual narratives across cultures and how general frameworks of visual narrative comprehension account for variations in situational (dis)continuity.